2008
DOI: 10.1634/theoncologist.2008-0036
|View full text |Cite
|
Sign up to set email alerts
|

EBV-Associated Lymphoproliferative Disorders: Classification and Treatment

Abstract: Since its discovery as the first human tumor virus, Epstein-Barr virus (EBV) has been implicated in the development of a wide range of B-cell lymphoproliferative disorders, including Burkitt's lymphoma, classic Hodgkin's lymphoma, and lymphomas arising in immunocompromised individuals (post-transplant and HIV-associated lymphoproliferative disorders). T-cell lymphoproliferative disorders that have been reported to be EBV associated include a subset of peripheral T-cell lymphomas, angioimmunoblastic Tcell lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
183
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(190 citation statements)
references
References 71 publications
2
183
0
1
Order By: Relevance
“…EBV is the causal agent of infectious mononucleosis (IM), a common benign disorder, and is associated with several human malignancies [22][23]. Worldwide, more than 95% of adults are infected with EBV [24], with the majority of infections occurring during childhood when they produce minimal symptoms.…”
Section: Ebv Life Cyclementioning
confidence: 99%
“…EBV is the causal agent of infectious mononucleosis (IM), a common benign disorder, and is associated with several human malignancies [22][23]. Worldwide, more than 95% of adults are infected with EBV [24], with the majority of infections occurring during childhood when they produce minimal symptoms.…”
Section: Ebv Life Cyclementioning
confidence: 99%
“…Necropsies were performed at each facility after death (case Nos. [2][3][4][5] 16 but additional analysis was performed in the present study.…”
Section: Animalsmentioning
confidence: 99%
“…Besides in situ hybridization for EBER, immunohistochemistry is used to detect EBV-related antigens, including EBV-encoded nuclear antigen 2 (EBNA2) and latent membrane protein 1 (LMP1). 5 Although a previous study suggested that an LMP1 antibody did not cross-react with macaque LCV antigen, 28 cells reacting with an EBNA2 antibody have been detected in sections of lymphomas in rhesus and cynomolgus macaques (Macaca fascicularis). 2,4,10,20,24,28 Therefore, immunostaining for EBNA2 is a possible option for detecting LCV in Japanese macaques.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…It accounts for 7-10% of all non-Hodgkin's lymphomas diagnosed in East Asia and Latin America, but only 1% of such lymphomas among Caucasians (1)(2)(3). Among the risk factors for NKTL development, Epstein-Barr virus (EBV) latent infection has been shown to play an important role, and ENKTL is closely associated with EBV infection (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%